Glycolthermal synthesis of Bi2MoO6 nanoplates and their photocatalytic performance - Phattranit Dumrongrojthanath (2018)
© 2015 Elsevier B.V. Bi2MoO6 nanoplates were successfully synthesized by a glycolthermal method at 160 °C for 12 h. Pure orthorhombic Bi2MoO6 nanoplates were characterized by X-ray diffraction, scanning electron microscopy and UV-visible absorption spectroscopy. The effect of reaction temperature and length of reaction time on phase and morphology of the as-synthesized products was investigated. The 2.75 eV energy gap was investigated by UV-visible spectroscopy and was responsible for the photocatalysis. Photocatalytic performance of the Bi2MoO6 nanoplates evaluated through the degradation of rhodamine B under Xe light irradiation was 98.20% within 120 min.